Understanding student-teachers’ teaching method preferences and rationales: insights from selected university colleges in Tanzania - Rugambuka, Innocent Buberwa (Papers in Education and Development, 2024)
This study reports the teaching method preferences and rationales of student-teachers from Dar es Salaam and Mkwawa University Colleges of Education. A questionnaire with closed and open-ended items was administered to 335 participants and analysed through descriptive statistics and thematically. The findings indicated that transmission-based methods, particularly lectures, were slightly preferred most, while interactive ones, such as group discussions, were somewhat less preferred. The provided reasons for preferring transmission methods include content coverage, teaching time, frequency of use, class size, and improvement of listening and note-taking skills. The reasons for interactive methods were that they encourage participation, collaboration, confidence, knowledge sharing, and stimulation of critical thinking and creativity. The study concludes that the lecture method remains the dominant university teaching approach, partly because learners prefer it. However, the benefits of interactive learning cannot be ignored. Thus, the study recommends blending traditional lectures with interactive elements to enhance student engagement and participation.